„NEC TEMERE NEQUE INIUSTE, SED CONSULTO ET AEQUITATIS DUCTU IN HANC TERRAM TRANSVECTUS SUM” (GG II, 12) – LEGITYMIZOWANIE WŁADZY W GESTA GUILLELMI WILHELMA Z POITIERS - Dżwigała, Bartłomiej (Saeculum Christianum. Pismo Historyczne, 2017)
The aim of the article is to analyse first medieval biography of William the Conqueror in order to explain the issue of legitimization of the Norman rule in England. In the introduction I present the author of Gesta Guillelmi and his work. Main part of the article contains detailed explanatory narrative’s elements used by author to provide ideological justifications for William the Conqueror’s rule in London.